2016
DOI: 10.1007/s00198-015-3470-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E homologues α- and γ-tocopherol are not associated with bone turnover markers or bone mineral density in peri-menopausal and post-menopausal women

Abstract: We did not find biologically meaningful results between dietary and tocopherol homologues with BTMs or BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…The relationship between vitamin E (particularly αTF), inflammation, and bone health has been investigated in a large cohort study of older women consisting of two visits (first visit: 1997–1999, age: 55 ± 2.2 years, n = 3883; second visit: 2007–2011, age: 66 ± 2.2 years, n = 2130). In this study, Yang et al (2016) found a positive association between serum αTF and BMD at the femoral neck, but a negative association between serum αTF and inflammation, evidenced by higher concentrations of IL-6 and high-sensitivity C-reactive protein (hs-CRP), among participants not taking vitamin E supplements [73].…”
Section: Molecular Actions Of Vitamin E On Bonementioning
confidence: 90%
“…The relationship between vitamin E (particularly αTF), inflammation, and bone health has been investigated in a large cohort study of older women consisting of two visits (first visit: 1997–1999, age: 55 ± 2.2 years, n = 3883; second visit: 2007–2011, age: 66 ± 2.2 years, n = 2130). In this study, Yang et al (2016) found a positive association between serum αTF and BMD at the femoral neck, but a negative association between serum αTF and inflammation, evidenced by higher concentrations of IL-6 and high-sensitivity C-reactive protein (hs-CRP), among participants not taking vitamin E supplements [73].…”
Section: Molecular Actions Of Vitamin E On Bonementioning
confidence: 90%
“…On the other hand, Odai et al’s cross-sectional study showed that dietary intake of vitamin E was associated with higher bone mineral density in premenopausal women but had no effect in postmenopausal women [ 202 ]. Yang et al found no effect of vitamin E on bone turnover markers or bone mineral density in peri- or postmenopausal women in the UK [ 203 ]. The antioxidant properties of vitamin E and their beneficial effects on other bone cells such as osteoblasts might be the confounding factors leading to these conflicting results [ 204 ].…”
Section: Recent Pre-clinical Studiesmentioning
confidence: 99%
“…However, subsequent studies demonstrated that 1) aged αTTP knockout mice had reduced cortical bone mass, 2) low dietary Vitamin E intake did not increase bone mass in mature rats, 3) high dietary Vitamin E intake did not reduce cortical bone mass in mature rats, and 4) high Vitamin E intake did not affect cortical bone mass in maturing rats [5,6]. Human studies, likewise, have shown conflicting results regarding the beneficial or detrimental effects of Vitamin E on bone health [7][8][9][10][11][12][13]. Thus, the role of Vitamin E in bone remains unclear and somewhat controversial.…”
Section: Introductionmentioning
confidence: 99%